2020
DOI: 10.1002/jbmr.4166
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ Promote Periosteal Osteoblast Precursor Expansion and Differentiation for Fracture Repair

Abstract: In response to bone fracture, periosteal progenitor cells proliferate, expand, and differentiate to form cartilage and bone in the fracture callus. These cellular functions require the coordinated activation of multiple transcriptional programs, and the transcriptional regulators Yes‐associated protein (YAP) and transcriptional co‐activator with PDZ‐binding motif (TAZ) regulate osteochondroprogenitor activation during endochondral bone development. However, recent observations raise important distinctions betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Both signaling pathways are known for their strong osteoanabolic effects during bone regeneration. (7,(36)(37)(38)(39) On the other hand, known inhibitors of canonical Wnt signaling (eg, Dkk1, Dkk3, Sclerostin) were also significantly enriched in the fracture callus, although these molecules were shown to have a negative effect on fracture healing. (10,14,40,41) This might be due to a negative feedback loop for self-regulation of the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Both signaling pathways are known for their strong osteoanabolic effects during bone regeneration. (7,(36)(37)(38)(39) On the other hand, known inhibitors of canonical Wnt signaling (eg, Dkk1, Dkk3, Sclerostin) were also significantly enriched in the fracture callus, although these molecules were shown to have a negative effect on fracture healing. (10,14,40,41) This might be due to a negative feedback loop for self-regulation of the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that YAP and TAZ coordinately enhanced osteoblast activity and osteoclast-mediated bone remodeling to promote bone development 48 . In addition, YAP appears to be involved in the expansion and differentiation of periosteal osteoblastic precursor cells in order to promote bone fracture healing 49 . Interestingly, YAP has been shown to be associated with the osteocyte-mediated bone remodeling processes by regulating the mechanical properties of bone matrix organization 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, YAP/TAZ could contribute to bone fracture healing because YAP/TAZ deletion in adult mice impaired bone formation in the callus ( Kegelman et al, 2021 ). Thus, YAP/TAZ accelerated bone fracture healing via the expansion and differentiation of periosteal osteoblast precursors.…”
Section: Yap/taz and Bone Biologymentioning
confidence: 99%